Importance of Serum Adiponectin Levels in The Prediction And Ethiopathogenesis of Intrauterine Growth Restriction - KarlÄ±, Pervin; BaÅŸbuÄŸ, Alper; KÄ±lÄ±Ã§, Ã‡iÄŸdem; Kutluer, GÃ¼lÅŸen; Artar, Ä°shak; GÃ¼lerman, Hacer Cavidan (Journal of Medical Biomedical and Applied Sciences, 2018)
Objective: Our aim in this study is to determine the possibility that patients with IUGR (intrauterine growth retardation)will be able to look at the adenonetin levels in the early stages of pregnancy and to have IUGR. In this respect, earlydiagnosis, treatment and follow-up are aimed to reduce morbidity and mortality due to IUGRMaterial Method: The study was carried out between January and March 2010. Zekai Tahir Burak WomenÃ¢â¬â¢s HealthEducation and Research Hospital 28-40. with 89 patients aged 18-40 years. Groups 44 IUGR patients and 45 normalpregnant patients were divided into two groups. To examine the serum adiponectin level, an average of 3 cc was takenin the gel biochemistry tubes and then centrifuged at 4000 10 minutes. The resulting serum samples were collectedfor the ELISA kit and kept at -80 C until the day the patients were collected. In the study, adiponectin levels weremeasured by serum ELISA (enzyme linked immunosorbent assay) method.Results: In adiponectin evaluation, mean value was 105.90 19.02 pg / ml for the IUGR group, 65.96 16.5 pg / mlfor the control group and 1.6 times higher for the IUGR group( p < 0.001)Conclusion: In this study, the increased adiponectin levels of IUGR patients were significantly higher than those ofIUGR patients, suggesting that pregnancies of IUGR patients can be measured high in the first weeks and if IUGR ishigh in those weeks, IUGR can be predicted.